A short caspase-3 isoform inhibits chemotherapy-induced apoptosis by blocking apoptosome assembly. - Frédérique Végran (Public Library of Science (PLoS), 2011)
Alternative splicing of caspase-3 produces a short isoform caspase-3s that antagonizes caspase-3 apoptotic activity. However, the mechanism of apoptosis inhibition by caspase-3s remains unknown. Here we show that exogenous caspase-3 sensitizes MCF-7 and HBL100 breast cancers cells to chemotherapeutic treatments such as etoposide and methotrexate whereas co-transfection with caspase-3s strongly inhibits etoposide and methotrexate-induced apoptosis underlying thus the anti-apoptotic role of caspase-3s. In caspase-3 transfected cells, lamin-A and α-fodrin were cleaved when caspase-3 was activated by etoposide or methotrexate. When caspase-3s was co-transfected, this cleavage was strongly reduced. Depletion of caspase-3 by RNA interference in HBL100 containing endogenous caspase-3s caused reduction in etoposide and methotrexate-induced apoptosis, whereas the depletion of caspase-3s sensitized cells to chemotherapy. In the presence of caspase-3s, a lack of interaction between caspase-3 and caspase-9 was observed. Immunoprecipitation assays showed that caspase-3s binds the pro-forms of caspase-3. This result suggested that the absence of interaction with caspase-9 when both variants of caspase-3 are present contribute to block the apoptosome assembly and inhibit apoptosis. These data support that caspases-3s negatively interferes with caspase-3 activation and apoptosis in breast cancer, and that it can play key roles in the modulation of response to chemotherapeutic treatments.